EFEKTIVITAS PAJAK PROGRESIF KENDARAAN RODA DUA PADA SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) DI WILAYAH BOGOR - Zulfahmi, Jilfy; Syamsah, T.N (JURNAL ILMIAH LIVING LAW, 2018)
Identification of this research are1) How is the progressive taxâs effectiveness of two-wheeled vehicles in the Bogor Regionâs Samsat? 2) What are the obstacles and efforts made by the regional government to overcome the implementation of progressive taxes? 3) What is the solution to implementing a fair progressive tax between the government and taxpayers?. The research method used in this research is the normative juridical approach, namely the law is conceptualized as norms, rules, principles or dogmas/jurisprudence. The result of this research are: 1) implementation of progressive tax of two-wheeled vehicle at Samsat City Bogor and Bogor Regency not yet optimal; 2) Inhibiting factors that occur in the implementation of progressive tax on motorcycle taxpayers include: Inhibiting factors for officers in the field, facilities and infrastructure factors, community factors as taxpayers; 3) Solutions are given to overcome the inhibiting factors, namely: Adding facilities and infrastructure in the form of samsat corner in the mall, samsat to pick up the ball with samsat around, Samsat City Office Bogor and Bogor regency also facilitate taxpayers who do report on the sale of vehicles motor that has been sold for the taxpayer is not subject to progressive tax.